Deciphering the Mechanism of Human Carbonic Anhydrases Inhibition with Sulfocoumarins: Computational and Experimental Studies. Issue 31 (3rd May 2018) - Nocentini, Alessio; Carta, Fabrizio; Tanc, Muhammet; Selleri, Silvia; Supuran, Claudiu T.; Bazzicalupi, Carla; Gratteri, Paola
Abstract: The reaction mechanism of the carbonic anhydrase‐mediated hydrolysis of sulfocoumarins to sulfonic acids has been investigated on an enzyme cluster model using the B3LYP hybrid density functional theory (DFT) and the QST procedure for the Transition State (TS) search. A multistep process was highlighted, with the rate‐determining step identified in the initial dual nucleophilic/acidic attack of the zinc‐bound hydroxide ion to the sulfocoumarin sulfur atom and to the C3=C4 double bond. The reported multi‐step process, combined to SAR analysis on a new set of derivatives, highlighted unprecedented mechanistic aspects of the CA‐mediated prodrug activation, which in turn possess relevant consequences to the isoforms‐selective inhibition profiles reported by such a class of compounds. Abstract : A multistep process for the carbonic anhydrase (CA)‐mediated hydrolysis of sulfocoumarins highlighted unprecedented mechanistic aspects of the CA‐mediated prodrug activation.